4-(4-Bromophenyl)-7,7-dimethyl-2-methylamino-3-nitro-7,8-dihydro-4H-chromen-5(6H)-one including an unknown solvate - S. Antony Inglebert; Jayabal Kamalraja; K. Sethusankar; Gnanasambandam Vasuki (Acta Crystallographica Section E, 2014)
In the title compound, C18H19BrN2O4, the chromene unit is not quite planar (r.m.s. deviation = 0.199 Å), with the methyl C atoms lying 0.027 (4) and 1.929 (4) Å from the mean plane of the chromene unit. The six-membered carbocyclic ring of the chromene moiety adopts an envelope conformation, with the dimethyl-substituted C atom as the flap. The methylamine and nitro groups are slightly twisted from the chromene moiety, with C—N—C—O and O—N—C—C torsion angles of 2.7 (4) and −0.4 (4)°, respectively. The dihedral angle between the mean plane of the chromene unit and the benzene ring is 85.61 (13)°. An intramolecular N—H...O hydrogen bond generates an S(6) ring motif, which stabilizes the molecular conformation. In the crystal, molecules are linked via N—H...O hydrogen bonds, forming hexagonal rings lying parallel to the ab plane. A region of disordered electron density, most probably disordered ethanol solvent molecules, occupying voids of ca 432 Å3 for an electron count of 158, was treated using the SQUEEZE routine in PLATON [Spek (2009). Acta Cryst. D65, 148–155]. Their formula mass and unit-cell characteristics were not taken into account during refinement.